2023
DOI: 10.3201/eid2901.220975
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology and Carriage of Diphtheria in Epidemic-Prone Area and Implications for Vaccination Policy, Vietnam

Abstract: D iphtheria is an infectious disease caused by toxigenic strains of Corynebacterium diphtheriae, C. ulcerans, and, rarely, C. pseudotuberculosis (1-3). Although the diphtheria toxoid vaccine contributed to a decrease in the number of diphtheria cases globally, the disease remains a threat to public health, particularly in South and Southeast Asia (4,5).Currently, the World Health Organization recommends 3 primary doses of the diphtheria-tetanuspertussis (DTP) vaccine in young infants (i.e., at 6, 10, and 14 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…This study observed a lower proportion of participants with a confirmed history of DPT vaccination in Quang Ngai than that in Nha Trang. In addition, our previous study detected a lower seroprevalence of anti-diphtheria toxoid IgG among children aged 1–5 years in Quang Ngai (36%) than in Nha Trang (68%) [ 12 ]. A similar pattern was observed with a lower prevalence of an anti-PT IgG of ≥62.5 IU/mL (29%) among the ages 0–2 years in Quang Ngai compared with that in Nha Trang (48%) in this study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study observed a lower proportion of participants with a confirmed history of DPT vaccination in Quang Ngai than that in Nha Trang. In addition, our previous study detected a lower seroprevalence of anti-diphtheria toxoid IgG among children aged 1–5 years in Quang Ngai (36%) than in Nha Trang (68%) [ 12 ]. A similar pattern was observed with a lower prevalence of an anti-PT IgG of ≥62.5 IU/mL (29%) among the ages 0–2 years in Quang Ngai compared with that in Nha Trang (48%) in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It is an area with limited health access due to its mountainous topography, where three diphtheria cases were reported between January and September 2019. A total of 1500 participants were approached for enrollment as follows: 350, 400, 400, and 350 for age groups 1–5, 6–17, 18–40, and 41–55 years, respectively, based on the previously measured diphtheria seroprevalence in Vietnam using multi-stage cluster sampling [ 12 ]. This survey was originally conducted for diphtheria serosurveillance.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations